SCIENTIFIC AND THEORETICAL BASIS FOR THE DEVELOPMENT OF STUDENTS' LINGUOMETHODOLOGICAL THINKING BASED ON THE PRINCIPLES OF AN INTEGRATIVE APPROACH - Yuldashev Sodiq Norchayevich; Mahmudova Shodiyaxon Qobil qizi (American Journals, 2025)
The article examines the possibilities of developing students' linguistic and methodological thinking based on the principles of an integrative approach, principles of an integrative approach, linguistic and methodological thinking.
Keywords: Principles of an integrative approach, linguistic and methodological thinking, critical thinking, cross-cultural approach, multidisciplinarity.